A q-Rung Orthopair Fuzzy Set Extension of the DEMATEL and Its Application in the Education Sector - Helen Revalde; Porferio Almerino Jr.; Michelle Rodriguez; Pamela Hortelano; Mylen Revalde; Catherine Chan; Sherwin Kenneth Sabellano; Genelyn Sevare; Jennefer Fortela; Lorna Cacha; Maria Lizel Manos; Procila Mateo; et al. (Advances in Fuzzy Systems)
The need to address the impediments to teaching numeracy in early childhood education necessitates a comprehensive approach, as an evident lack of exploration of impediments and their intertwined relationships exists in the domain literature. Thus, this work advances such agenda by utilizing the decision-making trial and evaluation laboratory (DEMATEL) approach with q-rung orthopair fuzzy sets (q-ROFSs), referred to as q-ROF-DEMATEL. Unlike other fuzzy set extensions, q-ROFS offers a larger decision space, providing the capability to handle information with greater ambiguity. The proposed q-ROF-DEMATEL is applied to identify the critical factors impeding effective instruction of numeracy skills to early childhood learners. The findings suggest that the prominent impediments include inadequate teaching time, lack of teaching knowledge, and underestimation of learners’ knowledge. Moreover, among the identified impediments, the lack of teaching knowledge emerges as the key impediment, while language barriers, inadequate teaching time, and lack of educational resources are identified as minor key impediments. These findings could guide decision makers in academic institutions to allocate resources effectively, pool human resources strategically, and develop appropriate strategies to augment teaching numeracy. Investing in professional development opportunities, incorporating visual representations and culturally relevant materials, and seeking community partnerships for resources are some recommended initiatives to address these challenges. Insights for future work were outlined.